Halogenation for improvement of storage Life of chilli (Capsicum annuum L.) seeds - Navya P (Department of Seed Science and Technology, College of Horticulture, 2016)
An experiment ‘Halogenation for improvement of storage life in chilli (Capsicum annuum L.) seeds’ to standardise the optimum dose and mode of halogenation of chilli seeds and to evaluate the storage potential of halogenated seeds under ambient storage condition was conducted in Department of Seed Science and Technology, College of Horticulture, Vellanikkara during 2014-16.Seeds of two chilli varieties Ujwala and Anugraha were utilized for the study. Calcium oxy chloride (CaOCl2), iodine crystal (I2) and potassium iodide (KI) were the halogens used. Seeds were treated with halogens either alone or in combination with a carrier (CaCO3). Performance of treated seeds was compared to untreated control (T1). The halogen treatments comprised of each halogen at two doses viz.CaOCl2 @ 2g per kg of seeds (T2), CaOCl2 @ 4g per kg of seeds (T3), Iodine crystal @ 50mg per kg of seeds (T4), Iodine crystal @ 100mg per kg of seeds (T5), KI @ 50mg per kg of seeds (T6) and KI @100mg per kg of seeds (T7). In addition, seeds were also treated with a combination of halogen and carrier (CaCO3) in equal proportions (T8 to T13). After dry dressing the seeds with halogen or halogen carrier combination it was packed in 400G polyethylene bag and stored under ambient conditions. Seed quality parameters were recorded at monthly intervals for a period of 14 months. With the advancement of storage period, germination (%) declined irrespective of the treatments in both the varieties. Irrespective of the varieties throughout the storage period, performance of treated seeds was found to be superior over control irrespective of the varieties. In var. Ujwala, at the end of storage (14th month) high germination per cent was recorded in seeds treated with iodine crystal + CaCO3 @ 50mg each per kg of seeds followed by CaOCl2 +CaCO3 @ 4g each per kg of seeds. Seed treatment with CaOCl2 @ 2g per kg of seeds and CaOCl2@ 4g per kg of seeds were found to be the lower.Combination treatments such as iodine crystal + CaCO3 @ 50mg per kg of seeds , CaOCl2 + CaCO3 @ 2g each per kg of seeds, CaOCl2 + CaCO3 @ 4g each per kg of seeds and KI+ CaCO3 @ 50mg each per kg of seeds retained germination per cent above Minimum seed certification standards(MSCS) till 9th month of storage while in untreated seeds viability was retained only upto 5th month. Similarly in the case of parameters like vigour indices and dehydrogenase activity, seed treatment with iodine crystal + CaCO3 @50mg each per kg of seeds and CaOCl2 +CaCO3 @ 4g each per kg of seeds were found to be superior. In case of electrical conductivity of seed lechate a higher value was observed in untreated control while the least was recorded in seed treatment with Iodine crystal + CaCO3 @ 50mg each per kg of seeds. In var. Anugraha, high germination per cent was recorded in seeds treated with CaOCl2 + CaCO3 @ 2g each per kg of seeds, iodine crystal + CaCO3 @100mg each per kg seed and iodine crystal + CaCO3 @50mg each per kg of seeds. These treatments retained germination per cent above MSCS till 12th month of storage where as untreated seeds were viable only upto 9 months. Electrical conductivity of seed lechate was least in seeds treated with CaOCl2 + CaCO3 @ 2g each /kg of seeds compared to the highest value in untreated control. Microflora infection was found to be lower in halogenated seeds when compared to control in both the varieties. The major organisms observed were Aspergillus niger, Aspergillus flavus, Pencillium sp. The results indicated that seed treatment with halogens was highly beneficial in enhancing the storage life of chilli. Iodine crystal with carrier @50mg each per kg of seeds and CaOCl2 with carrier @ 2g each per kg of seeds may be recommended. Seed treatment with halogens therefore provides a cheaper method to enhance seed viability and seedling performance under ambient storage condition.